Basal rot of Chamelaucium uncinatum caused by Phytophthora nicotianae in Argentina - Palmucci, Hemilse Elena (2013)
Since 1995 severe losses were recorded on the production of Chamelaucium uncinatum in the vicinity of La Plata. In 2010, with the aim to confirm the identity of the causal agent of Geraldton waxplant basal rot, molecular studies were added to the morphological observations of the pathogen. P. nicotianae was identified as the causal agent of the disease.